Subliminal mortality salience does not increase physical strength output in double-blind randomized controlled trial - Bartenschlager, Christopher T. J.; Jansen, Petra (Frontiers in Psychology, 2023)
Introduction Using the morality salience paradigm, this research tested whether subliminal death stimuli lead to increased physical strength. Moreover, it was investigated if mindfulness and self-esteem instability influence terror management. Methods In total, data from 160 undergraduate sports students were analyzed. Participants completed a word decision task in which they were presented with either the word death or pain for 28.5 ms. Before and after the task, their grip strength was measured using a hand dynamometer. Results Linear mixed models could neither confirm the effect of the mortality salience hypothesis on strength nor an influence of mindfulness and self-esteem. Discussion The results raise the question of a potential influence of subliminal mortality salience on athletic performance and how mindfulness and self-esteem instability affect terror management.